2014
DOI: 10.1155/2014/963961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles in Photosynthetic Plants

Abstract: Nanobiotechnology is emerging as a field of applied biological science and nanotechnology. Synthesis of nanoparticles is done by various physical and chemical methods but the biological methods are relatively simple, cost-effective, nontoxic, and environmentally friendly methods. The present review focuses on the synthesis of nanoparticles with special emphasis on the use of plants parts for the synthesis process, its applications, and future prospectus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(95 citation statements)
references
References 51 publications
(46 reference statements)
3
91
0
1
Order By: Relevance
“…It was reported that plants extracts contain biomolecules including polyphenols, ascorbic acid, flavonoids, sterols, triterpenes, alkaloids, alcoholic compounds, polysaccharides, saponins, β-phenylethylamines, glucose and fructose, and proteins/enzymes which could be used as reductant to react with silver ions and therefore used as scaffolds to direct the formation of AgNPs in the solution (Prasad, 2014). It was also considered that some biomolecules like glucose and ascorbate reduce AgNO₃ and HAuCl 4 to form nanoparticles.…”
Section: Mechanismmentioning
confidence: 99%
“…It was reported that plants extracts contain biomolecules including polyphenols, ascorbic acid, flavonoids, sterols, triterpenes, alkaloids, alcoholic compounds, polysaccharides, saponins, β-phenylethylamines, glucose and fructose, and proteins/enzymes which could be used as reductant to react with silver ions and therefore used as scaffolds to direct the formation of AgNPs in the solution (Prasad, 2014). It was also considered that some biomolecules like glucose and ascorbate reduce AgNO₃ and HAuCl 4 to form nanoparticles.…”
Section: Mechanismmentioning
confidence: 99%
“…However, microorganism-mediated synthesis of AgNPs possesses multi-step procedures like microbial isolation, culture preparation, maintenance, etc. which is tedious and timeconsuming compared to plants [1,18,23]. Several studies have reported that biomolecules from plant extracts such as polyphenols, flavonoids, alkaloids, essential oils, proteins, enzymes, polysaccharides, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that biomolecules from plant extracts such as polyphenols, flavonoids, alkaloids, essential oils, proteins, enzymes, polysaccharides, etc. have the excellent power to reduce silver ions and effectively cape the produced AgNPs inhibiting agglomeration and thus providing good stability of the particle [5,16,17,23]. In this study, silver nanoparticles have been synthesized successfully using aqueous extract of leaves of Citrus maxima Merr.…”
Section: Introductionmentioning
confidence: 99%
“…The physical methods include evaporation-condensation and laser ablation [11]. Biological methods employ microorganisms, plant extracts, or enzymes for the synthesis of AgNPs [12][13][14]. Plants are considered better option than microorganisms due to their availability, nontoxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%